'I thought all you needed for a successful class was a desk and paper … ': shifting pedagogies in pre-service teachers' drawings of early childhood classrooms. Issue 4 (4th July 2021) - Rech Penn, Leslie; Lee, Kyunghwa; Capuozzo, Robert; Pase, Francesca
ABSTRACT: This paper draws on data from an ongoing study on pre-service (PS) teachers' perceptions of early childhood/elementary classrooms, conducted during a university course on arts and creativity in early childhood education (ECE). The study focuses on PS teachers' perspectives on arts and material pedagogies in ECE classrooms via pre- and post-class drawings of an ideal classroom and written reflections. The findings reveal that PS teachers' perceptions of and experience with materials and environment in the classroom may have a direct influence on ways they incorporate materials and environment in their future pedagogies. The study also shows ways in which university coursework and field experiences both compliment and come into tension with one another. We conclude with implications for early childhood/elementary teacher education.